Platelet-rich plasma in the pathologic processes of tendinopathy: a review of basic science studies - Lu, Jialin; Li, Han; Zhang, Ziyu; Xu, Rui; Wang, Jincheng; Jin, Hui (Frontiers in Bioengineering and Biotechnology, 2023)
Tendinopathy is a medical condition that includes a spectrum of inflammatory and degenerative tendon changes caused by traumatic or overuse injuries. The pathological mechanism of tendinopathy has not been well defined, and no ideal treatment is currently available. Platelet-rich plasma (PRP) is an autologous whole blood derivative containing a variety of cytokines and other protein components. Various basic studies have found that PRP has the therapeutic potential to promote cell proliferation and differentiation, regulate angiogenesis, increase extracellular matrix synthesis, and modulate inflammation in degenerative tendons. Therefore, PRP has been widely used as a promising therapeutic agent for tendinopathy. However, controversies exist over the optimal treatment regimen and efficacy of PRP for tendinopathy. This review focuses on the specific molecular and cellular mechanisms by which PRP manipulates tendon healing to better understand how PRP affects tendinopathy and explore the reason for the differences in clinical trial outcomes. This article has also pointed out the future direction of basic research and clinical application of PRP in the treatment of tendinopathy, which will play a guiding role in the design of PRP treatment protocols for tendinopathy.